Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/jfpp.16309
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐assisted extraction of anthocyanin from black rice bran using natural deep eutectic solvents: Optimization, diffusivity, and stability

Abstract: The present study was aimed to establish a green extraction method for anthocyanins from black rice bran using natural deep eutectic solvents (NADES) coupled with ultrasound-assisted extraction (UAE). Initially, five NADES were used and lactic acid: fructose was screened as an efficient extractant for anthocyanin from black rice bran.The extraction condition was optimized using an artificial neural network-genetic algorithm and the best condition was found to be time 11.25 min, water 12.63%, solventto-solid ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…The results exhibited that the amount of anthocyains extracted from UAE was less than that obtained by PEF and MAE under similar extraction time. Ultrasound waves during UAE are attributed to mechanical effects of cell disruption on black rice pericarp, and increased solvent diffusion leading to enhance ultrasonic capillary effect (Thakur et al, 2022). These effects are similar to the effects UAE on other plant materials (Yin et al, 2022;Zhong & Wang, 2010).…”
Section: Effect Of Assisted-extraction Techniques On the Grain Surfac...mentioning
confidence: 81%
“…The results exhibited that the amount of anthocyains extracted from UAE was less than that obtained by PEF and MAE under similar extraction time. Ultrasound waves during UAE are attributed to mechanical effects of cell disruption on black rice pericarp, and increased solvent diffusion leading to enhance ultrasonic capillary effect (Thakur et al, 2022). These effects are similar to the effects UAE on other plant materials (Yin et al, 2022;Zhong & Wang, 2010).…”
Section: Effect Of Assisted-extraction Techniques On the Grain Surfac...mentioning
confidence: 81%
“…This phenomenon, known as cavitation, leads to tiny bubbles' formation and rapid collapse. The collapse of these bubbles generates intense local pressures and temperatures, disrupting cell walls or breaking molecular bonds, facilitating the release of desired compounds [13][14][15][16]29]. Whereas the PEF method involved the use of electric current, caused structural changes in the cell membranes, and induced severe cracking in the cell walls of the Kao-Kum Doi-Saket.…”
Section: Effect Of Various Extraction Methods On Total Anthocyanin Co...mentioning
confidence: 99%
“…As shown in Table 4, these by-products are major sources of natural rutin, flavonoids, and anthocyanins. As a green and sustainable extraction medium, DESs have extracted polyphenols from wheat barn [73] and brewer spent grain [72], anthocyanin from black rice bran [74], and rutin from tartary buckwheat hull [75]. The polyphenol-rich NADESs extract from foxtail millet bran was mainly composed of coumaric acid, apigenin-C-dihexoside, and p-coumaroylspermidine, and showed high acetylcholinesterase inhibitory activity [76].…”
Section: Cereal By-productsmentioning
confidence: 99%
“…Fick's model successfully forecasted the extraction kinetics of tannic acid using an ultrasound-assisted DESs extraction method and revealed that diffusivity was the controlling factor [57]. Kinetic studies showed that the extraction diffusivity of anthocyanin in NADESs (1.063 × 10 −12 ) was markedly higher than in water (0.835 × 10 −12 ) [74]. Moreover, it has been reported that DESs extracted more polyphenols with higher molecular weights and more diverse phenolic compounds than methanol from mangosteen peel [43].…”
Section: Dess and Its Mechanism Of Polyphenol Extractionmentioning
confidence: 99%
See 1 more Smart Citation